Development of a tentacle propulsion technique for underwater application - Tarik, Alamgir; Rashid, Muhammad Mahbubur; Khan, Md. Raisuddin (2013)
As robotic technology matures and more platforms are fielded in unstructured real-world situations, the more new areas of applications are being thought for robotic deployment. After successes in industrial robots, researchers are now trying to explore new robots with biological features of different biological creatures like, snake, bird, and spider for their stunning advantages. Underwater exploration using robots is a new avenue. Research on the tentacle robot for underwater application is a new field of research besides the other research in this arena. There are few researches on this topic are explored and mostly are on biological robot. Besides those researches this paper aims to propose and demonstrate another technique to build a tentacle for propulsion purposes. Therefore, in this paper will discuss more on mathematical development for the propulsion technique and its software verification technique in considering the environmental constrains.